Osteocrin, a bone-derived humoral factor, exerts a renoprotective role in ischemia–reperfusion injury in mice. Issue 3 (5th October 2021) - Nishiguchi, Yoshihiko; Hata, Yusuke; Date, Ryosuke; Fujimoto, Daisuke; Umemoto, Shuro; Kanki, Tomoko; Yokoi, Hideki; Mori, Keita P; Handa, Takaya; Watanabe-Takano, Haruko; Kanai, Yugo; Yasoda, Akihiro; et al.
ABSTRACT: Background: Osteocrin (OSTN), a bone-derived humoral factor, was reported to act on heart and bone by potentiating the natriuretic peptide (NP) system. Ostn gene polymorphisms have been associated with renal function decline, but its pathophysiological role in the kidney remains unclear. Methods: The role of endogenous OSTN was investigated using systemic Ostn -knockout (KO) mice. As a model for OSTN administration, liver-specific Ostn -overexpressing mice crossed with KO (KO-Tg) were generated. These mice were subjected to unilateral ischemia–reperfusion injury (IRI) and renal lesions after 21 days of insult were evaluated. A comprehensive analysis of the Wnt/β-catenin pathway was performed using a polymerase chain reaction (PCR) array. Reporter plasmid-transfected proximal tubular cells (NRK52E) were used to investigate the mechanism by which OSTN affects the pathway. Results: After injury, KO mice showed marginal worsening of renal fibrosis compared with wild-type mice, with comparable renal atrophy. KO-Tg mice showed significantly ameliorated renal atrophy, fibrosis and tubular injury, together with reduced expressions of fibrosis- and inflammation-related genes. The PCR array showed that the activation of the Wnt/β-catenin pathway was attenuated in KO-Tg mice. The downstream targets Mmp7, Myc and Axin2 showed similar results. MMP7 and Wnt2 were induced in corticomedullary proximal tubules after injury, but not in KO-Tg. In NRK52E, OSTN significantly potentiated the inhibitory effects of NP on transforming growth factor β1–induced activation of the Wnt/β-catenin pathway, which was reproduced by a cyclic guanosine monophosphate analog. Conclusions: Ectopic Ostn overexpression ameliorated subsequent renal injury following ischemia–reperfusion. OSTN could represent possible renoprotection in acute to chronic kidney disease transition, thus serving as a potential therapeutic strategy.